2020 COVID-19 American Academy of Clinical Neuropsychology (AACN) Student Affairs Committee survey of neuropsychology trainees. Issue 7 (16th November 2020) - Guidotti Breting, Leslie M.; Towns, Stephanie J.; Butts, Alissa M.; Brett, Benjamin L.; Leaffer, Emily B.; Whiteside, Douglas M.
Abstract: Objective: To conduct an online survey in order to understand neuropsychology trainees' perspectives during the COVID-19 pandemic and identify pertinent concerns, training gaps, and recommendations. Method: A total of 874 neuropsychology trainees (81% female) completed the 69-item survey. Of the included trainees, 48% were doctoral students, 17% were interns, and 35% were postdoctoral residents (50% of resident respondents were in their first year). Results: The majority of neuropsychology trainees reported some impact of the pandemic on their professional and/or personal life. Overall, the impact did not differ by training level, geographic location, or demographic factors. Trainees' primary professional concerns included uncertainty about the impact of the pandemic on their professional future, loss of clinical hours, and desire for increased and ongoing communication from their leadership. A notable percentage of trainees reported increased personal mental health symptoms (i.e. anxiety/depression; 74%/54%), as well as a number of other personal stressors. Despite the transition to telehealth (mostly interviews/feedback sessions), few trainees have prior training or experience in providing neuropsychological services via phone or video platform. A limited proportion of trainees (approximately 10%) were still seeing patients face-to-face for neuropsychological evaluations during the COVID-19 pandemic as of 14 April 2020. Conclusions: The COVID-19 pandemic is impacting neuropsychological training and the well-being of trainees. This survey highlights the importance of communication with trainees during uncertain times. Based on the survey results, recommendations were developed to assist neuropsychology organizations in developing initiatives to support trainees during the current pandemic and in the future.